A Review of Von Hippel-Lindau Syndrome - Varshney, Neha (J Kidney Cancer VHL, 2017)
Von Hippel-Lindau syndrome (VHL) is a familial neoplastic condition seen in approximately 1 in 36,000 live births. It is caused by germline mutations of the tumor suppressor gene VHL, located on the short arm of chromosome 3. While the majority of the affected individuals have a positive family history, up to 20% of cases arise from de novo mutations. VHL syndrome is characterized by the presence of benign and malignant tumors affecting the central nervous system, kidneys, adrenals, pancreas, and reproductive organs. Common manifestations include hemangioblastomas of the brain, spinal cord, and retina; pheochromocytoma and paraganglioma; renal cell carcinoma; pancreatic cysts and neuroendocrine tumors; and endolymphatic sac tumors. Diagnosis of VHL is prompted by clinical suspicion and confirmed by molecular testing. Management of VHL patients is complex and multidisciplinary. Routine genetic testing and surveillance using various diagnostic techniques are used to help monitor disease progression and implement treatment options. Despite recent advances in clinical diagnosis and management, life expectancy for VHL patients remains low at 40–52 years. This article provides an overview of the major clinical, histological, and radiological findings, as well as treatment modalities.